A Half-Inverse Problem for Impulsive Dirac Operator with Discontinuous Coefficient - Yalçın Güldü (Abstract and Applied Analysis)
An inverse problem for Dirac differential operators with discontinuity conditions and discontinuous coefficient is studied. It is shown by Hochstadt and Lieberman's method that if the potential function in is prescribed over the interval , then a single spectrum suffices to determine on the interval and it is also shown here that is uniquely determined by a spectrum.